Respuesta :
[tex]\text {Hi! Let's Solve this Equation!}[/tex]
[tex]\text {The First Step is to Simplify the Equation:}[/tex]
[tex]\text {3 becomes 3x. 3*-2=-6 so that becomes -6.}[/tex]
[tex]\text {Add: -6+4=-2}[/tex]
[tex]\text {Your new Problem should be: 3x+-6+4=2x-1}[/tex]
[tex]\text {The Next Step is to Subtract 2x:}[/tex]
[tex]\text {3x-2-2x=2x-1-2x}\\\text {x-2=-1}[/tex]
[tex]\text {The Final Step is to Add 2:}[/tex]
[tex]\text {x-2+2=-1+2}[/tex]
[tex]\text {Your Answer should be:}[/tex]
[tex]\fbox {x=1}[/tex]
[tex]\text {Best of Luck!}[/tex]
[tex]\text {-LimitedX}[/tex]
Answer:
- 1
Step-by-step explanation:
Step 1:
3 ( x - 2 ) + 4 = 2x - 1 Equation
Step 2:
3x - 6 + 4 = 2x - 1 Multiply
Step 3:
3x - 2 = 2x - 1 Combine Like Terms
Step 4:
3x = 2x - 1 + 2 Add 2 on both sides
Step 5:
3x = 2x - 1 Combine Like Terms
Step 6:
x = - 1 Subract 2x on both sides
Answer:
x = - 1
Hope This Helps :)